Language teachers’ job-related emotions, emotional intelligence, and outlook on academic life - Vez López, Enrique (Universitas Negeri Semarang, 2025)
Academic work can put a lot of pressure on professors, which can trigger emotional distress. This study attempted to shed light into how a group of language teachers deal with emotions produced by job stress in their academic settings. The objective was to find out how they coped with job-related stress and emotions and whether these impacted their emotional framework, their sense of satisfaction, and their expectations of academic growth. To collect the data, a mixed methods approach was used. Interviews were carried out after two surveys were administered to professors from two universities: one in Brazil and the other in Mexico. The findings point out to mixed feelings on the part of the participants. The feel happy and take pride in working for a university; however, feelings of inadequacy, pessimism, anxiety, discouragement, and stress sometimes set in because of strong competition and difficulty to earn a full-time position.